COMPARATIVE CHRONOLOGY OF THE PREHISTORY OF THE AREA BETWEEN THE VISTULA AND DNIEPER: 3150-1850 BC - Klochko, Victor I.; Kośko, Aleksander; Szmyt, Marzena (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 1999)
This volume of the Baltic Pontic Studies focuses on the results of the research carried out so far into the absolute (radiocarbon) chronology of the area lying between the Vistula and Dnieper or the bio-cultural borderland between the West and East of Europe. Absolute chronology is treated here both as a research goal and fundamental premise in the broader studies of the chronometrie and development synchronization of "borderland" cultural systems. In a series of articles devoted to individual taxa a considerable number of new 14C dates have been compared. The dates concern source materials that have been chosen from the point of view of their representativeness and chronometrie value ("short-lived" materials were preferred to minimize a potential error). The vast majority of analyses were purposefully made in the same 14C laboratory of the State Scientific Center of Environmental Radiogeochemistry of Ukrainian Academy of Sciences in Kiev taking advantage of funds generously provided by the Polish Committee for Scientific Research. The volume devoted to the "dark" section of the "borderland" history (3150-1850 BC) is the first but not the last publication on the broader issues mentioned above that we intend to present in the near future.